2021
DOI: 10.1016/j.jhep.2020.10.016
|View full text |Cite
|
Sign up to set email alerts
|

HCC surveillance after SVR in patients with F3/F4 fibrosis

Abstract: HCV eradication by antiviral treatment reduces but does not eliminate HCC risk. Patients with established cirrhosis require HCC surveillance "indefinitely" after sustained virologic response (SVR) because they appear to have a high risk of HCC even many years after SVR. Patients without established or known cirrhosis may still require surveillance after SVR if they have a sufficiently high HCC risk. In all patients who achieve SVR, the key question is how we can reliably estimate HCC risk, and the change in HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 44 publications
2
107
0
1
Order By: Relevance
“…Finally, we agree with others that stopping the surveillance of low-risk groups is questionable, and that the intensification of screening programs in intermediate- or high-risk groups is a challenge that would improve compliance with surveillance recommendations. [3] , [4] , [5] , 10 , [28] , [29] , [30] …”
Section: Discussionmentioning
confidence: 99%
“…Finally, we agree with others that stopping the surveillance of low-risk groups is questionable, and that the intensification of screening programs in intermediate- or high-risk groups is a challenge that would improve compliance with surveillance recommendations. [3] , [4] , [5] , 10 , [28] , [29] , [30] …”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to identify high-risk patients, mainly based on biochemical, elastosonographic, multivariate, and deep learning models. 5 In particular, different models based on LSM values have been proposed for this purpose. 6,7,[21][22][23] However, none of the predictive models reported included variables reflecting the severity of portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,[21][22][23] However, none of the predictive models reported included variables reflecting the severity of portal hypertension. 5 In their seminal paper, Faillaci et al 8 showed that large oesophageal varices and high levels of angiopoietin-2, a reflection of neoangiogenesis and extensive splanchnic collateralisation, were independent predictors of both HCC occurrence and recurrence after DAAs. This study strongly suggests that the role of DAA in liver carcinogenesis acts through the main predisposing condition: severe portal hypertension and the linked modification of hepatic and splanchnic microcirculation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations